Implementation and evaluation of the three action teaching model with learning plan guidance in preventive medicine course - Chen, Cai-Yun; Shi, Ta-La; Wang, Ruo-Yu; Li, Ning; Hao, Yi-Han; Zhang, Jia-Le; Tang, Ming; Liu, Sha; Qin, Guo-min; Mi, Wei (Frontiers in Psychology, 2024)
Background: Towards the close of the 20th century, Chinese scholars introduced a novel pedagogical approach to education in China, distinguished by its divergence from conventional teaching methods. This instructional strategy assumes a pivotal role in imparting indispensable medical knowledge to students within a meticulously structured and all-encompassing framework.Objective: The objective of this study is to assess the effectiveness of a novel teaching approach that integrates the three action teaching model with learning plan guidance within a preventive medicine course. Through this investigation, empirical evidence will be provided regarding the impact of utilizing learning guided by the three action teaching model with learning plan guidance as an innovative instructional method, thereby shedding light on its potential to enhance students' autonomous learning in the field of preventive medicine. Methods: The control group consisted of 48 students from Class 2 of clinical medicine in grade 2021, who were taught using the traditional classroom teaching mode. Meanwhile, Class 1 served as the experimental group comprising 47 individuals, who received instruction through the three-action teaching model with learning plan guidance. Evaluation was conducted using course tests and questionnaires, and data analysis was performed utilizing t-tests, analysis of variance, and rank sum tests in SPSS software.Results: The average total score of the test group (79.44±10.13) was significantly higher than that of the control group (70.00±13.57) (t=3.943, P<0.001). Moreover, there were more experimental groups with total scores ranging from 80 to 89 and 90 to 100 compared to the control group (Z=5.324, P=0.002). The Subjective Evaluation System (SES) indicated that the experimental group (69.11± 8.39)outperformed the control group (61.23±6.59) in terms of total scores (t=5.095, P<0.001), demonstrating superior performance in learning methods, emotions, engagement, and performance metrics (P<0.05). Specifically, analysis using the Biggs study process questionnaire revealed that the experimental group exhibited higher levels of deep learning (t=6.100, P<0.001) and lower levels of superficial learning (t=-3.783, P<0.001) when compared to the control group.Conclusions: The implementation of a novel teaching approach that integrates the three-action teaching model with learning plan guidance significantly enhances students' academic achievements and fosters their intrinsic motivation for learning.